Manajemen Bandwidth Dan Pengguna Jaringan Pada Universitas Atma Jaya Makassar - Sean Coonery Sumarta (TEMATIKA: Jurnal Penelitian Teknik Informatika dan Sistem Informasi, 2018)
This research is focus on how to optimize the usage of bandwidth at the University of Atma Jaya Makassar to provide fluency either online or offline while accessing the service of UAJM. In this research user management to be made using the Hotspot management and for Management bandwidth will be created using the queue tree and per connection queuing (PCQ). Queue tree used to allocate bandwidth to each user category and is used to divide the bandwidth PCQ fairly and evenly.